JURIDICAL ANALYSIS OF JUDICIAL CONSIDERATIONS IN NARCOTICS OFFENSES (CASE STUDY NUMBER 1838/PID.SUS/2025/PN MDN) - Tohom Reymond; Tri Reni Novita (Jurnal Ilmu Hukum dan Keadilan, 2026)
Category I narcotics based on Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics; to analyze the judges’ considerations in imposing criminal sanctions from the perspective of the individualization of punishment and the principle of justice; to examine the implementation of the principle of proportionality in sentencing and its impact on combating narcotics crimes; and to identify obstacles in the application of criminal law along with efforts to overcome them. The results of the study show that all elements of Article 114 paragraph (1) have been lawfully and convincingly fulfilled. The judges’ considerations in imposing punishment reflect the application of the principle of individualization of punishment and the principle of justice. The implementation of the principle of proportionality in sentencing is carried out by balancing the objectives of retribution, deterrence, and rehabilitation. The main obstacles in the application of narcotics criminal law lie in the limitations of proving distribution networks and a sentencing approach that remains predominantly repressive. Therefore, more comprehensive and equitable sentencing policies are required in combating narcotics crimes